Kecerdasan Spiritual dalam Pendidikan Agama Islam Perspektif Hadis - Awaluddin, Raisa Zuhra Salsabila; Resti Okvani Kartika; Zulkipli Lessy (SALIHA: Jurnal Pendidikan Islam, 2024)
The issues of the decline of spiritual intelligence, especially in terms of morals such as brawls, school dropouts, and pornography continue to be a problem in education. In education, every learner must have spiritual intelligence to be able to eliminate the above impacts. This study aims to provide an overview of the types of spiritual intelligence in education. The research method used a literature study. The data is sourced from articles or books related to the title discussed. Documentation is one of the data collection methods to obtain information in the form of writing from data sources. The conclusion is that Islamic religious education functions as a tool for solving problems in society, especially for today's youth by instilling Islamic values. The purpose of Islamic religious education is to provide direction and monitoring of behavior and social morals that are emphasized through Islamic religious education as a provision for future life. The aim of Islamic religious education, is to give birth to several characteristics of spiritual intelligence which become assets in which there is a ent of the Prophet's traditions. First, feeling the presence of Allah SWT. Second, being helpful to others. Third, being helpful to others. Fourth, being honest, and fifth, being serious.